The Lateral Epidermis Actively Counteracts Pulling by the Amnioserosa During Dorsal Closure - Lv, Zhiyi; Zhang, Na; Zhang, Xiaozhu; Großhans, Jörg; Kong, Deqing (Frontiers in Cell and Developmental Biology, 2022)
Dorsal closure is a prominent morphogenetic process during Drosophila embryogenesis, which involves two epithelial tissues, i. e. the squamous amnioserosa and the columnar lateral epidermis. Non-muscle myosin II-driven constriction in the amnioserosa leads to a decrease in the apical surface area and pulls on the adjacent lateral epidermis, which subsequently moves dorsally. The pull by the amnioserosa becomes obvious in an elongation of the epidermal cells, especially of those in the first row. The contribution of the epidermal cell elongation has remained unclear to dorsal closure. Cell elongation may be a mere passive consequence or an active response to the pulling by the amnioserosa. Here we found that the lateral epidermis actively responds. We analyzed tensions within tissues and cell junctions by laser ablation before and during dorsal closure, the elliptical and dorsal closure stages respectively. Furthermore, we genetically and optochemically induced chronic and acute cell contraction, respectively. In this way, we found that tension in the epidermis increased during dorsal closure. A correspondingly increased tension was not observed at individual junctions, however. Junctional tension even decreased during dorsal closure in the epidermis. We strikingly observed a strong increase of microtubules amount in the epidermis, while non-muscle myosin II increased in both tissues. Our data suggest that the epidermis actively antagonizes the pull from the amnioserosa during dorsal closure and the increased microtubules might help the epidermis bear part of the mechanical force.